Modernization of training of highly qualified croly swimmers on the basis of historiographical analysis of world records - Karpov, V. Yu.; Komarov, M. N.; Rodionova, I. A.; Porubaiko, L. N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the main directions of modernization of the training system for highly qualified freestyle swimmers based on a historiographic analysis of world records.